1998
DOI: 10.1016/s0954-6111(98)90515-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of C-reactive protein measurements in exacerbations of chronic obstructive pulmonary disease

Abstract: C-reactive protein (CRP) has been shown to be a useful and sensitive indicator of pyogenic infections in many clinical situations, including acute pneumonia and infective pulmonary exacerbations in cystic fibrosis patients. Exacerbations of COPD are often, but not always, associated with demonstrable infection. The value of CRP measurement in this situation has not been assessed. We have evaluated CRP measurement in 50 patients [age 71 +/- 8 (SD) years] who were admitted to hospital with clinical evidence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
18

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 10 publications
5
70
0
18
Order By: Relevance
“…These results are in favor of the proven fact that COPD is a systemic inflammatory disease which primarily affects the lungs [17][18][19][20] . Similar results were obtained in the studies which suggest that the reduced lung function in COPD is associated with increased levels of systemic inflammatory markers [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 94%
“…These results are in favor of the proven fact that COPD is a systemic inflammatory disease which primarily affects the lungs [17][18][19][20] . Similar results were obtained in the studies which suggest that the reduced lung function in COPD is associated with increased levels of systemic inflammatory markers [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 94%
“…10 -16 C-reactive protein (CRP), a known marker of systemic inflammation, has been shown to be elevated in patients with both stable COPD and during exacerbation. [17][18][19][20][21] Because elevations in CRP have also been linked to CAD, 22 it appears as though the pathogenesis of both COPD and CAD may stem from enhanced systemic inflammation. Interestingly, although the mortality rate from cardiovascular diseases is decreasing in the developed world, the mortality rate from COPD is in fact increasing, and COPD is the fourth leading cause of death in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…A systemic inflammatory response during an AE-COPD has been noted with increases in plasma fibrinogen, IL-6, C-reactive protein (CRP), and endothelin-1, all reported to increase during exacerbations (31)(32)(33)(34). Interestingly, one group has confirmed that the degree of systemic inflammation, shown by rising serum IL-6 and CRP levels, correlated with sputum and nasal inflammation (35).…”
Section: Pathogenesismentioning
confidence: 98%